The expansion of vanity of Simon in A Portrait of the Artist as a Young Man - Farahmandian, Hamid; Liu, Chaojian (Frontiers in Psychiatry, 2023)
An aggressive personality is a distorted personality with dark traits such as arrogance, a sense of power over others, and exploitation. As per Karen Horney’s theory of neurosis, all these traits make an individual, psychologically, neurotic, who is willing to go against other people in society. In this paper, drawing upon Horney’s theory, I study the aggressive personality of Simon in James Joyce’s A Portrait of the Artist as a Young Man from three aspects of frustrated selfishness, sense of dominance, and search for respect to make known his neurotic needs for power, admiration, prestige, exploitation and achievement and demonstrate that offensive conducts of Simon make him more insecure and leave him more aggressive toward everybody at home and society.